2015
DOI: 10.1353/hpu.2015.0135
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Intimate Partner Violence Experiences: Knowledge, Access, Utilization and Barriers to Utilization of Resources by Women of the African Diaspora

Abstract: Objective This study examined knowledge, access, utilization, and barriers to use of resources among Black women exposed to multiple types of intimate partner violence in Baltimore, Maryland and the U.S. Virgin Islands (USVI). Methods We analyzed quantitative survey data collected by 163 women recruited from primary care, prenatal or family planning clinics in Baltimore and the USVI. In addition we analyzed qualitative data from in-depth interviews with 11 women. Quantitative data were analyzed using descrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 34 publications
6
48
0
Order By: Relevance
“…The reported types were physical and psychological (verbal & emotional). This finding agreed with those of Osulah [20] in Kenya, and Sabria et al [25] in Maryland, USA which reported that result of IPV differs from physical to emotional and sometimes sexual and economical. The women stated on the consequences of daily and long term IPV such as emotional and physical injuries as experienced by the survivors.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The reported types were physical and psychological (verbal & emotional). This finding agreed with those of Osulah [20] in Kenya, and Sabria et al [25] in Maryland, USA which reported that result of IPV differs from physical to emotional and sometimes sexual and economical. The women stated on the consequences of daily and long term IPV such as emotional and physical injuries as experienced by the survivors.…”
Section: Discussionsupporting
confidence: 92%
“…In the current study abused women took many steps before divorce decision as keeping silence, patience, seeking family help, react with violence and give chance and take time to assess. Congruently, Sabria et al [25] in Maryland, USA studied: The cumulative violence exposures: black women"s responses and sources of strength, and clarified that some women extradite support from family members and friends who assisted them survive with the violence they experienced.…”
Section: Discussionmentioning
confidence: 99%
“…Although studies investigating the direct effect of single forms of IPV exposure on pregnant women's ANC services attendance are scarce, there are a few related ones from sub-Saharan Africa which suggest that IPV exposure may be a risk factor for poor ANC services attendance 18 41 42. One of the reasons suggested is lack of sufficient information about ANC services, and partners who directly or indirectly through threats or actual violence stop them from going to ANC clinics 42 43. This may not be true in Rwandan settings where there is a highly successful sensitisation and education effort by CHWs to support the community on health-related issues such as ANC services attendance 44.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the impact of trauma may lead to passive victims of IPV. Although many women have demonstrated adverse effects of IPV that may act as barriers from seeking help (Sabri et al, 2015), many women also adapt to abuse and develop strategies that promote survival in the midst of traumatic experiences (Abraham, 2005). …”
Section: Learned Helplessness Versus Survivor Theorymentioning
confidence: 99%